Multivisceral resection for locally advanced gastric cancer: A retrospective study - Yang, Yanpeng; Hu, Jianwen; Ma, Yongchen; Chen, Guowei; Liu, Yucun (The American journal of surgery, 2021)
Multivisceral resection may be the exclusive radical procedure for cT4b gastric cancer patients. However, most surgeons refuse to select surgery because of the theoretical higher mortality, morbidity and poorer prognosis. We retrospectively reviewed cT4b gastric cancer patients who underwent surgery from January 1,1997 to December 31,2018. The primary endpoint was overall survival. Short-term results and prognostic values of clinical and pathologic factors were also analyzed. Patients underwent multivisceral resection had an acceptable mortality and morbidity. The overall 5-year survival rate of multivisceral resection was higher than that of palliative surgery (P < 0.05). And independent prognostic factors of multivisceral resection were R+ resection, extensive lymph node involved (>15), vascular cancer emboli, and postoperative chemotherapy. Conclusions: cT4b gastric cancer patients underwent multivisceral resection experience acceptable mortality and morbidity. The independent prognostic factors for multivisceral resection were completeness of resection, extensive lymph node involvement (>15), vascular cancer emboli, and postoperative chemotherapy. •CT4b gastric cancer patients could benefit from multivisceral resection.•R0 resection is independent prognostic factor for multivisceral resection.•CT4bN3b gastric cancers should be excluded from multivisceral resection.•≥6 cycles chemotherapy should be performed after multivisceral resection.